Genetics : Analysis of Genes and Genomes - Hartl, Daniel L Jones, Elizabeth W (Jones and Bartlett Publishers, 2005)
"Genetics: Analysis of Genes and Genomes, Sixth Edition by Hartl and Jones presents the modern world of genetics: treating classical, molecular, and population genetics as unified subdisciplines in a field that, even in our post-genomic era, still goes by the name "genetics." This approach to teaching genetics is a logical progression in a time when the various subdisciplines of genetics are so closely interwoven." "Written by two renowned authorities in the field, Genetics, Sixth Edition provides the most current, clear, comprehensive, and balanced introduction to genetics and genomics at the college level."--Jacket.